Invasion biology hypotheses and evidence - Jeschke, Jonathan M.; Heger, Tina (CABI invasive species series ;, 2018)
This book, containing 18 chapters, combines the hierarchy-of-hypotheses (HoH) approach with hypothesis networks for invasion biology. This book aims to further develop the HoH approach by inviting critical comments (Part I), apply it to 12 major invasion hypotheses (Part II) and explore how it can be expanded to a hierarchically structured hypothesis network (Chapter 7 and Part III). It is important to also check out the companion website that features, for instance, data from the ~1100 studies analysed in Part II of the book. Importantly and as outlined in Chapter 17, this website will be further updated and developed to become a powerful web portal for invasion biology and other research disciplines in the future